Access denied? Exploring the causes of the low representation of women in senior executive positions within procurement. Issue 4 (October 2018) - Lawrence, Jennifer; Lonsdale, Chris; Le Mesurier, Nick
Abstract: Recent surveys report the representation of women in senior executive positions within procurement as both very low and lower than in other professions. In this paper, the authors explored the causes of this. The authors interviewed 41 female and male procurement professionals from a range of sectors and seniority levels. Different views were encountered, but overall the findings suggested that female advancement within procurement is affected by both generic organisational and procurement-specific impediments, including inadequate work design, male-dominated cultures, negative stereotypes, high levels of travel and an aggressive ethos that characterises many procurement functions. The latter was said to be greater where procurement functions lacked 'cultural maturity'. The findings suggested that both the procurement literature and procurement profession need to do more to address these impediments to female advancement. Ways forward are suggested. Highlights: The representation of women within senior procurement positions is very low. In the paper, the authors explore the causes of this via qualitative research. The findings suggest both generic and procurement-specific causes. The findings also suggested gradually improving conditions for female advancement. Nevertheless, more needs to be done by the procurement literature and profession.